Influence of solvent-free extraction of fish oil from catfish (Clarias magur) heads using a Taguchi orthogonal array design: A qualitative and quantitative approach - Jaydeep Dave; Ali Muhammed Moula Ali; Tanaji Kudre; Pikunthong Nukhthamna; Nishant Kumar; Marek Kieliszek; Sri Charan Bindu Bavisetty (My University, 2023)
This study aimed to efficiently utilize catfish heads, enhancing the oil extraction process while improving the cost-effectiveness of fish byproduct management. The study employed the wet rendering method, a solvent-free approach, utilizing a two-factor Taguchi orthogonal array design to identify critical parameters for optimizing oil yield and ensuring high-quality oil attributes. The extraction temperature (80-120°C) and time (5-25 min) were chosen as variables in the wet rendering process. Range analysis identified the extraction time as a more significant (p < 0.05) factor for most parameters, including oil yield, oil recovery, acid value, free fatty acids, peroxide value, and thiobarbituric acid reactive substances. The extraction temperature was more significant (p < 0.05) for oil color. Consequently, the wet rendering method was optimized, resulting in an extraction temperature of 80°C and an extraction time of 25 min, yielding the highest oil yield. This optimized wet rendering process recovered 6.37 g/100 g of oil with an impressive 54.16% oil recovery rate, demonstrating comparable performance to traditional solvent extraction methods. Moreover, Fourier transfer infrared spectra analysis revealed distinct peaks associated with triacylglycerols and polyunsaturated fatty acids (PUFA). The oil recovered under optimized conditions contained higher levels of PUFA, including oleic acid (189.92 μg/g of oil), linoleic acid (169.92 μg/g of oil), eicosapentaenoic acid (17.41 μg/g of oil), and docosahexaenoic acid (20.82 μg/g of oil). Volatile compound analysis revealed lower levels of secondary oxidation compounds under optimized conditions. This optimized wet rendering method offers practical advantages in terms of cost-efficiency, sustainability, reduced environmental impact, and enhanced oil quality, making it an attractive option for the fish processing industries. Future research possibilities may include the purification of the catfish head oil and its application in the food and pharmaceutical industries.
Keywords: Unsaturated fatty acid; Meat and Animal Product Quality